1998
DOI: 10.1038/sj.onc.1201651
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch repair deficiency leads to a unique mode of colorectal tumorigenesis characterized by intratumoral heterogeneity

Abstract: In order to determine the e ects of mismatch repair (MMR) de®ciencies in sporadic colorectal carcinomas, 45 such cancers were examined using a sensitive method called crypt isolation technique. Loss of heterozygosity (LOH) in the MSH2 or MLH1 gene was more frequently observed in replication error (RER) (+) carcinomas than in RER (7) carcinomas, which implied that loss of one normal allele could partly a ect repair capacity. MSH2 gene defects at both alleles were observed in two carcinomas, which showed severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1998
1998
2001
2001

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Intratumoral heterogeneity was observed in the majority of samples. Intratumoral heterogeneity in MLH1 and MSH2 gene alterations has previously been reported by Habano et al (1998) in sporadic colorectal cancer using a sensitive technique for allelic loss detection in different crypts within the same tumour after microdissection. This is therefore in agreement with our findings using immunohistochemistry, which has the benefits of being simpler and more convenient.…”
Section: Discussionmentioning
confidence: 79%
“…Intratumoral heterogeneity was observed in the majority of samples. Intratumoral heterogeneity in MLH1 and MSH2 gene alterations has previously been reported by Habano et al (1998) in sporadic colorectal cancer using a sensitive technique for allelic loss detection in different crypts within the same tumour after microdissection. This is therefore in agreement with our findings using immunohistochemistry, which has the benefits of being simpler and more convenient.…”
Section: Discussionmentioning
confidence: 79%
“…The results suggest that nuclear and mitochondrial genomes partly share the same DNA repair system. In our previous study (Habano et al, 1998), loss of the hMSH2 and hMLH1 genes was observed in 21% and 20% of the same series of colorectal carcinomas, respectively. However, mtDNA instability was not mtDNA instability in colorectal carcinoma W Habano et al associated with these gene defects, suggesting that a certain MMR enzyme other than hMSH2 or hMLH1 may be responsible for maintenance in both nuclear and mitochondrial genomes.…”
Section: Discussionmentioning
confidence: 99%
“…Corresponding tissue specimens were obtained from normal mucosa located distal to the tumor. All specimens were surgically resected at Iwate Medical University Hospital, Morioka, Japan, between 1993 and 1995, as described previously (Habano et al, 1998). Crypt isolation and total cellular DNA extraction were performed as previously described (Habano et al, 1996).…”
Section: Crypt Isolation and Dna Extractionmentioning
confidence: 99%
“…Plasmacytomas can therefore be added to the plethora of mouse models of human cancer (B cell lymphomas, 31 T cell lymphomas, 32 and other malignancies 33 ) that have been utililized successfully to study clonal diversity during oncogenesis. However, the possibility to associate clonal diversification processes with a pool of tumor/tumor progenitor cells, which is clearly defined by clonotypic T(12;15) translocations and monoclonal Ig production, may be a unique advantage of the BALB/c plasmacytoma system.…”
Section: Figurementioning
confidence: 99%